Evaluation of emission characteristics of a stoichiometric natural gas engine fueled with compressed natural gas and biomethane. (1st April 2021) - Lee, Sangho; Yi, Ui Hyung; Jang, Hyungjoon; Park, Cheolwoong; Kim, Changgi
Abstract: In this study, the performance and emission characteristics of a stoichiometric natural gas engine were investigated using biomethane and compressed natural gas (CNG). The wide-open throttle (WOT) test and world harmonized transient cycle (WHTC) mode were conducted using a 11 L class six-cylinder natural gas engine that satisfies the emission standards of EURO-6. The biomethane contained 98.69% CH4 content and had a low calorific value of 39.46 MJ/Nm 3 owing to the absence of C2–C4 hydrocarbons. In the WOT test, the engine performance deteriorated due to the poor combustion characteristics of biomethane. In particular, the thermal efficiency decreased by 2% when biomethane was used. The high CH4 content of biomethane increased the concentration of oxygenated hydrocarbons at the engine outlet. A total of 72%-76% of non-methane hydrocarbon (NMHC) was oxygenated in the WOT test using biomethane. In the WHTC mode, the emission standards of EURO-6 for nitrogen oxide, carbon monoxide, and NMHC were satisfied using biomethane. However, CH4 and ammonia emissions were higher than those specified in the EURO-6 emission standards when biomethane was used. Fuel consumption with biomethane was also 39.4% higher than that of CNG during the WHTC mode. Highlights: The torque and thermal efficiency decrease when biomethane was used. The composition of biomethane results in low C2–C4 hydrocarbon emissions. Low NOx formation leads to low ammonia formation when using biomethane. Biomethane does not satisfy the EURO-VI standards of CH4 and ammonia emissions.